2011
DOI: 10.1371/journal.pone.0018221
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Adult Mortality Due to 2009 Pandemic (H1N1) Influenza A in California

Abstract: BackgroundWhile children and young adults had the highest attack rates due to 2009 pandemic (H1N1) influenza A (2009 H1N1), studies of hospitalized cases noted high fatality in older adults. We analyzed California public health surveillance data to better characterize the populations at risk for dying due to 2009 H1N1.Methods and FindingsA case was an adult ≥20 years who died with influenza-like symptoms and laboratory results indicative of 2009 H1N1. Demographic and clinical data were abstracted from medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
48
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 12 publications
10
48
1
6
Order By: Relevance
“…The variations between these results can be justified by differences in the clinical severity of disease according to geographical region, climate and host adaptation 6 . The average time from symptom onset to death in our study was 13.9 days, which was similar to the time period of 14 days observed in California 17 . The rate of oseltamivir treatment was 88.6% in our study and was similar to the treatment rate of 80% observed in another study 17 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The variations between these results can be justified by differences in the clinical severity of disease according to geographical region, climate and host adaptation 6 . The average time from symptom onset to death in our study was 13.9 days, which was similar to the time period of 14 days observed in California 17 . The rate of oseltamivir treatment was 88.6% in our study and was similar to the treatment rate of 80% observed in another study 17 .…”
Section: Discussionsupporting
confidence: 86%
“…The average time from symptom onset to death in our study was 13.9 days, which was similar to the time period of 14 days observed in California 17 . The rate of oseltamivir treatment was 88.6% in our study and was similar to the treatment rate of 80% observed in another study 17 . Early treatment within 2 days after the onset of symptoms was significantly associated with a lower risk of emergency admissions and death in hospitalized patients who contracted the 2009 Pandemic Influenza A (H1N1) 20,21 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For example, clinical and epidemiological studies of the pandemic H1N1 virus infections worldwide suggested that rates of infection with the pandemic H1N1 2009 influenza virus differed significantly in different age groups, with children and young adults disproportionately susceptible to infection (4,24). Depending on the study and region analyzed, individuals under the age of 25 years represented 45% to 60% of infected subjects, though the pathogenic effects of H1N1 virus infection were most pronounced in individuals more than 60 years old (4,36). These findings, as well as recent immunological studies from our laboratory and other laboratories (11,17,20,22,25,33,39,48,51,52,55,61,62), suggest that previous encounters with vaccines or viruses provide immunological advantages and immunological memory in the population despite the "serological distance" between the hemagglutinin (HA) and neuraminidase (NA) proteins of seasonal and pandemic strains.…”
mentioning
confidence: 99%